A Novel Vector for Construction of Markerless Multicopy Overexpression Transformants in Pichia pastoris - Li, Ding; Zhang, Bo; Li, Shuting; Zhou, Jie; Cao, Hui; Huang, Yan; Cui, Zhongli (Frontiers in Microbiology, 2017)
Pichia pastoris is widely used as a platform for heterologous protein expression because of its high volumetric productivity. Multi-copy integration of the target gene is commonly used to improve the production of the target protein. Cre/lox recombination system is a powerful tool for the marker rescue during multiple integration with one selection marker. Here we reported a novel expression vector based on the Cre/lox recombination system for multiple integration of target gene to construct multi-copy expression strain of P. pastoris. PAOX1 promoter was fused to cre to construct a methanol inducible Cre recombinase. The leakage expression of Cre recombinase in Escherichia coli was blocked by introducing the operator gene lacO. The expression vector designed pMCO-AOXα was stable in E. coli and could effectively rescue the Zeocin resistance gene for next round of integration in P. pastoris. Phytase AppA from E. coli was chosen as a reporter gene. Transformants with 2-16 copies of appA were constructed by using a single antibiotic. Expression of appA was gene dosage dependent when less than 12 copies were integrated. The protein yield increased 4.45 folds when 12 copies of appA were integrated. Our results showed that pMCO-AOXα was highly effective for rational construction of multi-copy transformat in P. pastoris.